Implementasi Deep Learning Pembelajaran Berkualitas Dan Berorientasi Pada Pemahaman Konseptual Di SMA PGRI Pekanbaru - Ramadona, Aulia Ramadona; Ramadona, Aulia (Universitas Pahlawan Tuanku Tambusai, 2025)
Deep learning is that learning oriented towards conceptual understanding and critical thinking is a solution to improving the quality of education. This concept emphasizes the active involvement of students in exploration, analysis, and application of knowledge in real contexts. This study aims to determine and explore the application of deep learning in quality education strategies. Data were collected through interviews, observations, and document analysis. This study used a qualitative approach with a case study design to explore the implementation of deep learning in quality learning oriented towards conceptual understanding. The data sources consisted of teachers and students who had direct experience with this method, selected through purposive sampling. Data was collected through in-depth interviews, participatory observation, and document analysis. The results of this study show that if the steps are carried out consistently and collaboratively, deep learning has great potential to improve the effectiveness of the independent curriculum and shape students who are not only cognitively intelligent, but also reflective, critical, and have good character. The conclusion of this study is that the implementation of quality deep learning oriented towards conceptual understanding can improve the quality of education, critical thinking skills, and problem-solving abilities among students.